Route Optimization in Asymmetric Capacitated Vehicle Routing Problem (ACVRP) Model using Tabu Search Algorithm (Case Study: Car Oil Distribution of PT. Kencana Central Mobil) - Thedorus Junjun; Mariatul Kiftiah; Fransiskus Fran (Jurnal Matematika Sains dan Teknologi, 2024)
PT. Kencana Central Mobil is an automotive workshop that distributes oil to nine regular customers spread across Pontianak and its surroundings. The route from the depot to the customer and between customers has a different length, because when making a round trip using different roads. From this information, the author conducted observations in the field to measure the distance between customers with the help of the Avanza application. Thus, the problem in this company is included in the Asymmetric Capacitated Vehicle Routing Problem. The ACVRP model is a problem where the route from location  to  is not the same as the route from location  to . Based on the problems that have been explained, this study uses the Tabu Search algorithm to solve it. The Tabu Search algorithm works by moving from one route to another, so that when related to a problem the company can find a trip by choosing the shortest route. There are six steps in solving this problem, namely determining the initial route, finding alternative routes by swapping two node positions so that the routes that can be formed each iteration are  routes (nine is the number of customers), choosing the best route among alternative routes, determining the new best route, updating the tabu list and checking the stopping criteria. From the calculation results, there is a difference in the distance traveled from the initial route which is 63.16 km long, while when calculated using the Tabu Search Algorithm, it can be seen that the tabu search criteria stops at the 7th iteration with a route length of 50.26 km so that it differs by 12.9 km from the initial route. The length of the route is optimal because it has the shortest route length of all the literature that has been traced.